Science and the public: the public understanding of science and its measurements - Entradas, M. (Portuguese Journal of Social Science, 2015)
This is the first of a two-part historical review on the relationship between science and its publics in the second half of the twentieth century. The two-part literature review covers major trends in the evolution of this relationship from ‘public understanding of science’ (PUS) in which science was separated from laypeople, through the transition to ‘public participation’ when PUS became a matter for science policy. This first part of the literature describes the arguments that called for an increase in the public’s understanding of science, its measurement, and the academic debate in favour of and against PUS measures. In particular, we refer to the evolution of survey design, and how criticisms of measures of PUS gave rise to the ‘contextual’ perspective in the PUS being favoured over a ‘deficit’ one.